PERAN PENYULUH SWADAYA DALAM PENGEMBANGAN PRODUK TEH ORGANIK KELOMPOK TANI SUMBER TANI MUDA DESA CIPICUNG KECAMATAN CULAMEGA KABUPATEN TASIKMALAYA - Ilham Antapani Imanda; Ristina Siti Sundari; D Yadi Heryadi (Melati Institute, 2023)
In the agricultural sector, public sector services are urgently needed by people with commodity eyes in agriculture, one of the government service programs in agriculture, namely counseling. The role of agricultural extension workers is useful for increasing food production and increasing development. Counseling in Culamega District, Tasikmalaya Regency was carried out by PNS extension workers, THL (Freelance) extension workers, and self-help extension workers. One of the supporters of increasing the performance or development of organic tea farmers in Cipicung Village, Culamega District is that independent extension workers are responsible for helping extension workers and farmers to strengthen the relationship between extension workers and farmers. Organic tea is a tea plant that from land cultivation to processing results uses organic ingredients or without mixing chemicals or pesticides, in its fertilization it uses fertilizer from goat manure, roasted husks, and liquid organic fertilizer. This study aims to determine the effect of the role of independent extension workers on the development of organic products in Cipicung Village. The results of this study indicate that self-help extension agents play a role in the development of organic tea products in Cipicung Village, Culamega District.